Methocarbamol blocks muscular Nav1.4 channels and decreases isometric force of mouse muscles. Issue 1 (27th October 2020) - Zhang, Yaxin; Otto, Philipp; Qin, Lu; Eiber, Nane; Hashemolhosseini, Said; Kröger, Stephan; Brinkmeier, Heinrich
Abstract: Background: The muscle relaxant methocarbamol is widely used for the treatment of muscle spasms and pain syndromes. To elucidate molecular mechanisms of its action, we studied its influence on neuromuscular transmission, on isometric muscle force, and on voltage‐gated Na + channels. Methods: Neuromuscular transmission was investigated in murine diaphragm‐phrenic nerve preparations and muscle force studied on mouse soleus muscles. Nav 1.4 channels and Nav 1.7 channels were functionally expressed in eukaryotic cell lines. Results: Methocarbamol, at 2 mM, decreased the decay of endplate currents, slowed the decay of endplate potentials and reduced tetanic force of soleus muscles. The drug reversibly inhibited current flow through muscular Nav 1.4 channels, while neuronal Nav 1.7 channels were unaffected. Conclusions: The study provides evidence for peripheral actions of methocarbamol on skeletal muscle. Muscular Na + channels are a molecular target of methocarbamol. Since Nav 1.7 currents were unaffected, methocarbamol is unlikely to exert its analgesic effect by directly blocking Nav 1.7 channels.